Estimation of livestock excrement and its biogas production potential in China. (20th August 2019) - Bao, Weiqing; Yang, Yang; Fu, Tongcheng; Xie, Guang Hui
Abstract: The constant growth of livestock husbandry in China in recent years has raised grave concerns about severe environmental pollution. A countrywide, comprehensive assessment of the quantity and distribution of livestock excrement (LE) production could significantly promote contamination control methods and biogas development in China. Previous researchers have reported an excessively wide range of LE quantities and have failed to reach a consensus conclusion. By using the latest updated LE definitions and calculation coefficients, LE and its biogas potential were assessed for 14 types of livestock in this study according to China's husbandry statistics data. LE increased by 10.9% from 1563.2 Mt in 2007 to 1755.0 Mt in 2015 at a rate of 12.3% in fresh weight and increased by 12.8% from 367.1 Mt to 414.5 Mt in dry weight. The mean annual LE from 2013 to 2015 was estimated on a dry weight basis as 414.9 Mt. Most of the LE produced from 2013 to 2015 was by cattle (including draft cattle, beef cattle, and dairy cows), followed by sheep (including goats), poultry (including broiler chickens, egg chickens, ducks, and geese), pigs, and other livestock (including horses, donkeys, mules, camels, and rabbits). Among the six regions, from 2013 to 2015, the LE was distributed in ascending order in the Northwest, Northeast, Southwest, North, Central-south, and East regions on a dry weight basis. The average LE produced among the 31 provinces in China ranged widely from just 0.8 Mt (Shanghai) up to 42.4 Mt (Shandong), with the latter having the highest LE density distribution (275.7 t km -2 ) on a dry weight basis. The east-middle provinces, Liaoning, Shandong, Henan, Hebei, Tianjin, Jiangsu, and Anhui, exhibited relatively higher levels of LE density distribution (111.2–275.7 t km -2 ) than those of other regions. The yearly total LE generated from commercial scale husbandry feedlots (CSHF) for 2015 was estimated at 141.5 Mt, which amounts to a biogas potential of 60.6 billion m 3 (Billion refers 1 × 10 9 ). Scenario analysis predicts that by 2030, the annual LE from CSHF could range from 201.1 to 258.9 Mt, corresponding to biogas potential of 86–111 billion m 3 . The results of this countrywide study suggest that there are significant opportunities to improve LE management and to achieve ecological livestock husbandry in China. Highlights: Livestock excrement rose by 12.8% from 367 to 414 Mt (dry) in 2007–2015 in China. In 2013–2015, 36% of it was from cattle and 18–19% from sheep, pigs, and poultry. The 7 provinces in east-middle area showed highest excrement density distribution. The biogas potential of excrement from commercial feedlots was 6.1 × 10 10 m 3 in 2015. Biogas from it could range from 8.6 × 10 10 to 1.1 × 10 11 m 3 under 4 scenarios by 2030.